Iron-doped SiCw wave-absorbing material and preparation method thereof
By using reduced iron powder and Fe3O4 additives in the preparation of SiC whiskers, the method addresses growth and absorption issues, achieving enhanced electromagnetic wave absorption performance through optimized whisker growth and loss capacities.
Patent Information
- Application Number
- CN202411002434.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2024-12-13
AI Technical Summary
Existing methods for preparing SiC whiskers with iron doping do not achieve optimal electromagnetic wave absorption performance due to issues with whisker growth, impedance matching, and loss capacity, particularly when using ferrocene as an additive.
A method involving the use of reduced iron powder and Fe3O4 as iron-containing additives in the crosslinking process of high-hydrogen silicone oil, followed by mixing with carbon fiber and sintering at controlled temperatures to produce SiC whiskers, optimizing the growth and absorption properties.
The resulting SiC whiskers exhibit improved impedance matching, dielectric and magnetic loss capacities, with a 2.9GHz to 5.2GHz effective absorption bandwidth, and a composite material with 0.004 mol reduced iron powder showing the best comprehensive wave absorption performance.
Smart Images

Figure CN119136523A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials and relates to an iron-doped SiCw wave absorbing material and a preparation method thereof. Background Art
[0002] Using cheap high-hydrogen silicone oil as the silicon source and carbon source, iron-containing additives were added during the crosslinking process of the high-hydrogen silicone oil for doping, and then the crosslinked powder was mixed with carbon fiber to prepare SiC whiskers at high temperature. The results showed that SiC whiskers with added reduced iron powder and Fe3O4 showed good electromagnetic absorption and loss performance. When the content of each doped reduced iron powder and Fe3O4 was 0.002 mol, the whiskers produced had both good growth and wave absorption performance.
[0003] The general process of this experiment is to first use high hydrogen silicone oil under the catalysis of chloroplatinic acid alcohol solution to prepare the powder required for sintering SiC whiskers, and in this process, different types and contents of iron-containing additives are added, and then carbon fiber is used as the matrix for growing SiC whiskers and mixed with the prepared powder, and sintered into SiC whiskers in an inert atmosphere. The prepared whiskers are analyzed by X-ray diffraction, the morphology is observed by scanning electron microscopy, and the absorption performance is tested by vector network analyzer. Summary of the invention
[0004] An iron-doped SiCw absorbing material and a preparation method thereof, characterized in that the method comprises the following steps: Step 1: Use a measuring cylinder to take 20 ml of high hydrogen silicone oil into a large beaker, add a certain amount of chloroplatinic acid alcohol solution as a catalyst, and stir magnetically to make the chloroplatinic acid alcohol solution evenly dissolve in the high hydrogen silicone oil. Then add 0.001 mol of ferrocene, Fe2O3, reduced iron powder and Fe3O4, four different types of iron-containing additives, and stir evenly. Put the four solutions in a constant temperature drying oven at 120°C for static crosslinking. After all crosslinking into solids, put the obtained solids into an electric powder grinder for powdering. The prepared powder is passed through a 40-mesh standard sieve, and the unscreened particles are ground in a mortar and re-screened to obtain the final powder.
[0005] Step 2: Weigh the prepared powder and carbon fiber at a mass ratio of 100:1, pour all the weighed powder into the crucible, cut the carbon fiber into a suitable size and evenly mix it into the powder, set the heating process to 4°C per minute at the first 800°C, 2°C per minute from 800°C to 1600°C, and keep it at 1600°C for one hour and thirty minutes. After cooling to room temperature, take out the crucible, and use tweezers to separate the carbon fiber matrix of the SiC whisker growth from the sintered embedding powder. After grinding the prepared whiskers with a mortar, perform X-ray diffraction analysis, observe the morphology with a scanning electron microscope, and test its absorption performance with a vector network analyzer.
[0006] Step 3: After the test results come out, select the iron-containing additive material with good wave absorbing performance, change the added content under the same conditions to four different ratios of 0.001 mol, 0.002 mol, 0.003 mol, and 0.004 mol, and set up a blank control group to repeat the above experimental process.
[0007] Beneficial effects: 1) When different iron-containing additives are added, SiC whiskers can be generated, but the length of the SiC whiskers fired by adding ferrocene is shorter. In terms of wave absorption performance, the impedance matching of the SiC whiskers fired by adding ferrocene and Fe2O3 is not good, the refractive index is higher, and its dielectric loss capacity and magnetic loss capacity are also not as good as the SiC whiskers fired by adding reduced iron powder and Fe3O4. The SiC whiskers fired by adding reduced iron powder and Fe3O4 show a better impedance matching degree, and the effective absorption bandwidth for electromagnetic wave absorption below -10dB is 2.9GHz and 5.2GHz respectively. Its dielectric loss capacity and magnetic loss capacity are significantly stronger.
[0008] 2) When the content of reduced iron powder is changed, the sample with a doping amount of 0.002 mol has a higher absorption and loss capacity for electromagnetic waves than the samples with a doping amount of 0.001 mol and 0.003 mol, but lower than the sample with a doping amount of 0.004 mol. Although the whisker growth of the sample with a doping amount of 0.004 mol is not good, the ferrite exists in the fibril structure of the carbon fiber where the Si position replaces the C position. This structure itself has many defects, which is beneficial to the dielectric loss of the material to electromagnetic waves. Moreover, its loose and porous structure can make the electromagnetic waves reflect multiple times, which is beneficial to the ferrite, the fibril structure and the SiC whiskers to jointly adjust the material's wave absorption performance. Therefore, the composite material with a doping amount of 0.004 mol of reduced iron powder has the best comprehensive wave absorption performance.
[0009] 3) When the content of Fe3O4 doped is changed, the diameter of SiC whiskers doped with Fe3O4 is obviously much larger than that of undoped whiskers. At this time, a large liquid phase can be observed at the head of the SiC whisker. As the doping amount increases, the diameter of the head liquid phase increases, and the final length of the SiC whisker grows smaller. For samples with Fe3O4 doping amounts of 0.003 and 0.004 mol, the droplet-like structure at the whisker head is the largest, the whisker length is too small, and the ferrite exists in the large droplet-like structure, which retains the disadvantage of the high density of the ferrite itself. For samples with a doping amount of 0.002 mol, the whisker growth is better. Ferrite can adjust the wave absorption performance of the composite material together with SiC whiskers and fibril structures. Therefore, the 0.002 and 0.003 mol samples have similar electromagnetic wave absorption and loss capabilities. The material with better comprehensive performance is the sample with a doping amount of 0.002 mol. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 XRD curves of samples doped with different iron-containing additives; Figure 2 SEM images of samples doped with different iron-containing additives (a) Fe(C5H5)2; (b) Fe2O3; (c) Fe; (d) Fe3O4; Figure 3 The curves of the real and imaginary parts of the dielectric constant changing with frequency; Figure 3 The curves of the real and imaginary parts of the lower permeability changing with frequency; Figure 4 The reflectivity loss of the sample changes with frequency; Figure 5 The relationship between the dielectric loss and magnetic loss of the sample and the frequency (a) dielectric loss (b) magnetic loss; Figure 6 SEM images of SiC whiskers doped with different contents of reduced iron powder (a) undoped; (b) 0.001 mol; (c) 0.002 mol; (d) 0.003 mol; (e) 0.004 mol; Figure 7 Curves of the real and imaginary parts of the complex dielectric constant of the sample changing with frequency (a) real part of the dielectric constant (b) imaginary part of the dielectric constant. DETAILED DESCRIPTION
[0011] The specific steps are as follows: First, use a measuring cylinder to take 20 ml of high hydrogen silicone oil into a large beaker, add a certain amount of chloroplatinic acid alcohol solution as a catalyst, and stir magnetically to make the chloroplatinic acid alcohol solution evenly dissolve in the high hydrogen silicone oil. Then add 0.001 mol of ferrocene, Fe2O3, reduced iron powder and Fe3O4, four different types of iron-containing additives, and stir evenly. Put the four solutions in a constant temperature drying oven at 120°C for static crosslinking. After all crosslinking into solids, put the obtained solids into an electric powder grinder for powdering. The prepared powder is passed through a 40-mesh standard sieve. The unscreened particles are ground in a mortar and re-screened to obtain the final powder.
[0012] The prepared powder and carbon fiber are weighed at a mass ratio of 100:1, and all the weighed powder is poured into a crucible. The carbon fiber is cut into a suitable size and evenly doped in the powder. The heating process is set to 4°C per minute at the first 800°C, 2°C per minute from 800°C to 1600°C, and kept at 1600°C for one hour and thirty minutes. After cooling to room temperature, the crucible is taken out, and tweezers are used to separate the carbon fiber matrix of the SiC whisker growth from the sintered embedding powder. After the prepared whiskers are ground with a mortar, X-ray diffraction analysis is performed, the morphology is observed with a scanning electron microscope, and its absorption performance is tested with a vector network analyzer.
[0013] After the test results come out, select iron-containing additive materials with good absorbing performance, change the added content under the same conditions to four different ratios of 0.001 mol, 0.002 mol, 0.003 mol, and 0.004 mol, and set up a blank control group to repeat the above experimental process.
[0014] Effects of different iron-containing additives on the properties of SiC whiskers The XRD test results of the composite absorbing material containing SiC whiskers prepared by doping with different iron-containing additives are as follows. The iron-containing additives added are ferrocene, Fe2O3, reduced iron powder and Fe3O4, and the content is 0.001 mole of each substance added to every 20 ml of high hydrogen silicone oil.
[0015] The XRD curves of the samples doped with four different iron-containing additives all showed obvious and sharp peaks at diffraction angles (2θ) of 35.738°, 60.142°, and 71.969°. By comparing the standard SiC card with the MDI jade 6 software, it was confirmed that the obtained product did contain SiC, but it was necessary to observe by scanning electron microscopy whether SiC existed in the form of whiskers. Although four different iron-containing substances, namely ferrocene, Fe2O3, reduced iron powder and Fe3O4, were added in this experiment, no peaks related to these substances were observed in the XRD curve. This is because: according to the growth mechanism of SiC whiskers, the metal or metal compound catalyst added to the powder for sintering SiC whiskers cannot all enter the SiC whiskers, and the whisker growth is mostly a gas-liquid-solid (VLS) mechanism. The four iron-containing additives are introduced into the SiC whiskers as catalysts for whisker growth, and only exist in the droplet-shaped head during the gas-liquid-solid growth of the whiskers, with extremely low content. In addition, only crystals can be observed to have sharp peaks related to their properties through X-ray diffraction. Although the head liquid phase is cooled into a solid, it is not a crystal, so the presence of ferrite cannot be observed through XRD.
[0016] Depend on Figure 2It can be seen that SiC whiskers can be obtained from the samples doped with four different iron-containing additives. Among them, the silicon carbide whiskers doped with ferrocene are obviously different from the other three. The length of the SiC whiskers doped with ferrocene is mostly less than 10um, while the length of the SiC whiskers doped with the other three iron-containing additives is greater than 10um. The reason for this result may be that ferrocene has a low melting and boiling point. When the temperature exceeds 249℃, ferrocene exists in the crucible in the form of gas. When the temperature exceeds 400℃, ferrocene is easy to decompose. When the temperature rises to 1600℃, the gas phase produced by the decomposition of the residual ferrocene in the crucible affects the gas phase required for the growth of SiC whiskers. The melting points of the other three iron-containing additives are between 1500℃ and 1600℃, which will not have an adverse effect on the growth of SiC whiskers.
[0017] The real and imaginary parts of the complex dielectric constant and the real and imaginary parts of the magnetic permeability of the composite absorber containing SiC whiskers prepared by adding different iron-containing additives were measured by vector network analyzer in the frequency band from 2GHz to 18GHz, and the reflectivity loss and dielectric loss tangent of the four samples were calculated. tanδ ε and magnetic loss tangent tanδ μ .
[0018] Based on the above research results, we will conduct further research on the composite absorbing materials prepared by doping reduced iron powder and Fe3O4. By changing the content of reduced iron powder and Fe3O4 in high hydrogen silicone oil, we will explore the effect of doping amount on the phase composition, morphology and absorbing properties of silicon carbide whiskers.
[0019] By changing the doping content of reduced iron powder, 0.001, 0.002, 0.003, and 0.004 moles of reduced iron powder were added to every 20 ml of high hydrogen silicone oil, and a group of blank controls were set. The various test results of the sintered SiC whiskers are as follows: SEM images of SiC whiskers made by doping with different contents of reduced iron powder, of which the first one is a picture of SiC whiskers made without any iron-containing additives. It can be seen from the figure that there are many whiskers in the SEM photo of undoped SiC whiskers, which are overlapped in clusters of three-dimensional networks. The whiskers are thinner and longer in length, while the diameter of SiC whiskers made by doping with reduced iron powder is obviously larger than that of undoped whiskers. However, with the increase of reduced iron powder content, the density of SiC whiskers decreases and the length decreases. When the content of reduced iron powder is 0.004 mol, SiC whiskers are almost invisible in the SEM photo. The results show that the doping of trace amounts of reduced iron powder is conducive to the growth of SiC whiskers with larger diameters, but with the increase of its content, reduced iron powder will also affect the growth of SiC whiskers as a foreign impurity.
[0020] The curve of the real and imaginary parts of the complex dielectric constant of the samples with frequency. It can be seen from the figure that the real part ε' and imaginary part ε'' of the complex dielectric constant of the undoped SiC whisker do not fluctuate greatly with the increase of the electromagnetic wave frequency, and the curve is relatively gentle. The real part ε' and imaginary part ε'' of the dielectric constant of the four samples doped with different contents of reduced iron powder fluctuate greatly between 12GHz and 14GHz, and with the increase of the reduced iron powder content, this fluctuation trend gradually increases. The sample with a doping amount of 0.004 moles shows the largest fluctuation, and the sample with a doping amount of 0.001 moles shows the smallest. This is because the SiC in the sample or the carbon fiber fibril structure obtained by replacing the C position with the Si position is itself connected by covalent bonds. With the increase of the doping amount of reduced iron powder, the increase of ferrite in the final sintered sample can increase the carrier concentration of the sample, increase its conductivity, and make it present a higher complex dielectric constant.
[0021] The real and imaginary parts of the complex magnetic permeability of the samples change with frequency. The samples made by different reduced iron powder doping levels also show large fluctuations in the real part μ' and imaginary part μ'' of the magnetic permeability between 12GHz and 14GHz. Since the undoped SiC whiskers do not have magnetic loss capacity, the real part of their magnetic permeability is 1 and the imaginary part is 0. The real part μ' and imaginary part μ'' of the magnetic permeability of the sample with a doping amount of 0.004 mol have the strongest fluctuations, and the sample with a doping amount of 0.001 mol has the weakest. This shows that as the content of reduced iron powder added increases, the content of ferrite generated in the end also increases.
[0022] Figure 4 As shown: the four samples doped with reduced iron powder have the minimum reflectivity at 13GHz to 14GHz compared to the undoped samples, and the reflectivity at 14GHz to 18GHz is also lower than that of the undoped samples. As the doping amount increases, the sample with the lowest reflectivity is the sample with a doping amount of 0.004 mol, followed by the samples with 0.002 mol, 0.003 mol and 0.001 mol.
[0023] The relationship curves of dielectric loss and magnetic loss angle of the samples with frequency show that as the amount of reduced iron powder doping increases, its dielectric loss capacity and hysteresis loss capacity also increase accordingly, and also decrease in the order of 0.004 mol, 0.002 mol, 0.003 mol and 0.001 mol. The reason for this result may be that the SiC whiskers in the sample with 0.002 mol of reduced iron powder doping grow better, and its clustered structure, together with the corresponding ferrite content, improves the sample's absorption and loss capacity of electromagnetic waves, making its performance temporarily exceed that of the sample with 0.003 mol of doping. In addition, ferrite also exists in the carbon fiber fibril structure obtained by in-situ substitution. This in-situ substitution transforms the carbon fiber fibril into the fibril structure SiC, retains the porous structure, and enables electromagnetic waves to be reflected multiple times inside the material. It is equivalent to countless layers of absorption plates. The transmission distance of electromagnetic waves in the material increases, creating opportunities for ferrite to absorb electromagnetic waves multiple times. It also inherits the structural characteristics of the microfibrils formed by the folding of molecular chains, with a high content of microcrystals, and is easy to form a connected conductive network, showing higher conductivity, higher complex dielectric constant and dielectric loss, and is easy to improve the dielectric properties of SiC through interface polarization and multiple reflections. In the sample prepared by adding 0.004 mol of reduced iron powder, although there are few silicon carbide whiskers, ferrite can adjust the composite material's absorption and loss capacity of electromagnetic waves together with these fibril structures and a small amount of SiC whiskers, so that it reaches the best. In summary, the composite material with 0.004 mol of reduced iron powder has the best performance.
[0024] Although the samples doped with 0.004 and 0.003 mol of Fe3O4 have good wave absorption performance, the ferrite exists in a large droplet-like structure, which occupies the main body, so that the ferrite cannot be evenly present in the head of the whisker and the fibril structure to adjust the magnetic loss together with them. Such materials retain the disadvantage of ferrite itself as a wave absorbing material with high density, which cannot meet the requirements of light weight of future wave absorbing materials and should be abandoned. Although the sample doped with 0.002 mol of Fe3O4 is not as good as the sample doped with 0.003 mol in terms of content, its absorption and loss capacity of electromagnetic waves is the same as that of the sample doped with 0.003 mol. According to the SEM image, the ferrite existing in the whisker head, SiC whiskers and in-situ substituted fibril structure jointly adjust the wave absorption performance of the composite material. Therefore, the comprehensive performance of the sample doped with 0.002 mol of Fe3O4 is the best.
Claims
1. An iron-doped SiCw absorbing material and a preparation method thereof, characterized in that: The following steps are involved: First, use a measuring cylinder to take 20 ml of high hydrogen silicone oil into a large beaker, add a certain amount of chloroplatinic acid alcohol solution as a catalyst, and stir magnetically to make the chloroplatinic acid alcohol solution evenly dissolve in the high hydrogen silicone oil. Then add 0.001 mol of ferrocene, Fe2O3, reduced iron powder and Fe3O4, four different types of iron-containing additives, and stir evenly. Put the four solutions in a constant temperature drying oven at 120°C for static crosslinking. After all crosslinking into solids, put the obtained solids into an electric powder grinder for powdering. The prepared powder is passed through a 40-mesh standard sieve. The unscreened particles are ground in a mortar and re-screened to obtain the final powder.
2. The Fe-doped SiCw absorbing material and preparation method thereof according to claim 1, characterized in that: The prepared powder and carbon fiber are weighed at a mass ratio of 100:1, and all the weighed powder is poured into a crucible. The carbon fiber is cut into a suitable size and evenly doped in the powder. The heating process is set to 4°C per minute at the first 800°C, 2°C per minute from 800°C to 1600°C, and kept at 1600°C for one hour and thirty minutes. After cooling to room temperature, the crucible is taken out, and tweezers are used to separate the carbon fiber matrix of the SiC whisker growth from the sintered embedding powder. After the prepared whiskers are ground with a mortar, X-ray diffraction analysis is performed, the morphology is observed with a scanning electron microscope, and its absorption performance is tested with a vector network analyzer.
3. The Fe-doped SiCw absorbing material and the preparation method thereof according to claim 1, characterized in that: After the test results come out, select iron-containing additive materials with good absorbing performance, change the added content under the same conditions to four different ratios of 0.001 mol, 0.002 mol, 0.003 mol, and 0.004 mol, and set up a blank control group to repeat the above experimental process.
